Milk, mucosal immunity and the microbiome : impact on the neonate - Nestlé Nutrition Workshop (94th : 2019 : Lausanne, Switzerland); Aydogan, Cem; Berrington, Janet E.; Bode, Lars; Dunne-Castagna, Vanessa P.; Embleton, Nicholas D.; Ogra, Pearay L.; Walker, W. Allan; Lönnerdal, Bo 1938- (Switzerland : Karger, 2020)
Considerable advances have been made in science in order to understand the varied mixture of bioactive components in human milk. The 94th Nestlé Nutrition Institute Workshop was designed to provide a comprehensive overview of the latest findings in human milk research and its potential to modulate mucosal immunity, the microbiome, and its impact on the neonate. The publication provides a balanced state-of-the-art update on the current knowledge about milk, mucosal immunity, and the microbiome as well as their impact on breastfeeding in mammalian neonates. The first part reviews data on the immunology of milk and lactation from a historical perspective to the latest scientific findings. The second part discusses the microbiology of human milk and lactation in detail, with a focus on premature infants and necrotizing enterocolitis. And finally, in the third part, light is shed on the protective factors in human milk and their role in influencing the neonate's immune system. Important new insights will provide great scientific support for all people seeking a deeper understanding of human milk and its immunological properties and will enlarge the knowledge of those who have already specialized in human milk research.
La función de los autores fue determinada por el catalogador
Keywords: LECHE HUMANA -- CONGRESOS; LACTANCIA MATERNA -- CONGRESOS; MEMBRANA MUCOSA -- INMUNOLOGÍA -- CONGRESOS; LECHE HUMANA -- MICROBIOLOGÍA -- CONGRESOS; NIÑOS RECIEN NACIDOS; SISTEMA INMUNE